Application of the CIRC Model to Elementary School Students' Reading Comprehension Skills - Ni Nyoman Ayu Yuliastri; Ida Bagus Putrayasa; Dewa Bagus Sanjaya (MIMBAR PGSD Undiksha, 2025)
Students’ difficulties in reading comprehension remain a critical issue that hinders effective learning processes. Reading comprehension is an essential skill that must be developed to support academic success. This study aims to examine the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) model on students’ reading comprehension skills in relation to their reading interest. A quasi-experimental design was employed with a population of 155 students. Data were collected through reading comprehension tests and reading interest questionnaires, and analyzed using Two-Way ANOVA by level. The results revealed that: (1) there was a significant difference in reading comprehension between students in the experimental class and those in the control class; (2) a difference was found between the two classes among students with high reading interest; (3) a difference was also found among students with low reading interest; and (4) there was an interaction between the CIRC learning model and students’ reading interest in influencing reading comprehension. The findings conclude that the CIRC model is effective in enhancing reading comprehension, especially when students' reading interest is taken into account. These results imply the importance of selecting appropriate instructional models that align with students’ characteristics to optimize their reading comprehension skills.